Pemberian Habbatussauda’ Untuk Melancarkan Produksi Asi Pada Ibu Menyusui - Aisyah Miftahu Rosyidah; Sri Kustiyati (Pusat Riset dan Inovasi Nasional, 2023)
Background: The birthing process can affect breast milk production because it tends to cause lactogenesis to be slower. This is one of the factors why breast milk is not smooth at the beginning of the birth period. One treatment that can be done to facilitate breast milk production is by consuming Black Seed. Because black seed contains lagtogonum which functions to facilitate breast milk production. Objective: To determine the effect of giving black seed on the smooth production of breast milk in breastfeeding mothers at PMB Bidan Ning, Tawangmangu District. This research method uses a quasi-experimental method with a post test control group design. The research sample used accidental sampling, totaling 30 breastfeeding mothers on days 3-14 after giving birth who were divided into 2 groups, namely 15 control groups and 15 experimental groups. Results: The results of bivariate analysis using the Mann-Whitney test showed that the results for the black seed experimental group and the control group were p=0.000. Conclusion: There is a significant difference in the smoothness of breast milk between those given black seed and those not given black seed in PMB Bidan Ning, Tawangmangu District.